2015
DOI: 10.1039/c4ra13943g
|View full text |Cite
|
Sign up to set email alerts
|

Novel asymmetrical single- and double-chiral liquid crystal diads with wide blue phase ranges

Abstract: Novel asymmetrical single- and double-chiral liquid crystal diads are reported, where diad III-D exhibited the widest range of BPI about 31 °C. Large biaxiality and dipole moment of the bent molecule are useful to extend the BP temperature range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The hydrogen-bonded effects on supramolecular blue phase LCs of asymmetric H-bonded dimeric complexes D/P and D/P* are compared with their analogous covalent diads (see ref. 33), i.e., H-bonded dimeric complexes A*/P, A/P* and A*/P* vs. covalent diads A*-P, A-P* and A*-P*, respectively. 33…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrogen-bonded effects on supramolecular blue phase LCs of asymmetric H-bonded dimeric complexes D/P and D/P* are compared with their analogous covalent diads (see ref. 33), i.e., H-bonded dimeric complexes A*/P, A/P* and A*/P* vs. covalent diads A*-P, A-P* and A*-P*, respectively. 33…”
Section: Resultsmentioning
confidence: 99%
“…33), i.e., H-bonded dimeric complexes A*/P, A/P* and A*/P* vs. covalent diads A*-P, A-P* and A*-P*, respectively. 33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al 23 prepared a series of asymmetric hydrogen bonded complexes 57b-c,d-d*/47a-a** and also prepared complexes with different molar ratios of proton donors (57b-c,dd*) and proton acceptors (47a-a*). Further, they studied their mesomorphic properties and compared them with their analogous covalent diads reported by Wei et al 24 Scheme 7 shows the synthetic route for the preparation of the hydrogen bonded complexes. Hydrogen bond donors 57b-c,d-d* were synthesized by stirring 56b-c,d-d* and 10% Pd/C catalyst in THF solvent under hydrogen atmosphere at room temperature overnight.…”
Section: Pyridine-based Molecules As Thermotropic Mesogensmentioning
confidence: 99%
“…20 Pivnenko et al have reported that dimeric materials could stabilize the blue phase and enlarge its temperature range ca. The diad structures of BPLCs have been reported by our group recently, 26 which are novel asymmetrical liquid crystal diads with a central chiral flexible linker to link two different mesogenic cores. 21 In the meanwhile, it is a very common idea and a helpful strategy to use polymeric structures to stabilize and extend the BP temperature ranges.…”
Section: Introductionmentioning
confidence: 99%